Renal function estimations and dose recommendations for dabigatran, gabapentin and valaciclovir: a data simulation study focused on the elderly. Issue 4 (11th April 2013) - Helldén, Anders; Odar-Cederlöf, Ingegerd; Nilsson, Göran; Sjöviker, Susanne; Söderström, Anders; Euler, Mia von; Öhlén, Gunnar; Bergman, Ulf
Abstract : Objectives: The thrombin inhibitor dabigatran is mainly excreted by the kidneys. We investigated whether the recommended method for estimation of renal function used in the clinical trials, the Cockcroft-Gault (CGold ) equation and the estimated glomerular filtration rate (eGFR) modification of diet in renal disease equation 4 (MDRD4), differ in elderly participants, resulting in erroneously higher dose recommendations of dabigatran, which might explain the serious, even fatal, bleeding reported. The renally excreted drugs gabapentin and valaciclovir were also included for comparison. Design: A retrospective data simulation study. Participants: Participants 65 years and older included in six different studies. Main outcome measure: Estimated renal function by CG based on uncompensated ('old Jaffe' method) creatinine (CGold ) or by MDRD4 based on standardised compensated P-creatinine traceable to isotope-dilution mass spectrometry, and the resulting doses. Results: 790 participants (432 females), mean age (±SD) 77.6±5.7 years. Mean estimated creatinine clearance (eCrCl) by the CGold equation was 44.2±14.8 ml/min, versus eGFR 59.6±20.7 ml/min/1.73 m 2 with MDRD4 (p<0.001), absolute median difference 13.5, 95% CI 12.9 to 14.2. MDRD4 gave a significantly higher mean dose (valaciclovir +21%, dabigatran +25% and gabapentin +37%) of all drugs (p<0.001). With MDRD4 58% of the women would be recommended a full dose of dabigatran compared with 18% if CGold is used. Conclusions: MDRD4 would result in higher recommended doses of the three studied drugs to elderly participants compared with CG, particularly in women, and thus increased the risk of dose and concentration-dependent adverse reactions. It is important to know which method of estimation of renal function the Summary of Products Characteristics was based on, and use only that one when prescribing renally excreted drugs with narrow safety window. Doses based on recently developed methods for estimation of renal function may be associated with considerable risk of overtreatment in the elderly.